Implications of Kaon Condensation in Dense Nuclear Matter for Recent Light Compact Star Observations - Veselsky, Martin; Koliogiannis, Polichronis; Petousis, Vlasios; Leja, Jozef; Moustakidis, Charalampos (HNPS Advances in Nuclear Physics, 2026)
Recent measurements of the compact star XTE J1814-338, with a mass of M=1.2-0.05+0.05 Mø and a radius of R=7-0.4+0.4 Km alongside those of HESS J1731-347, which has a mass of M=0.77-0.17+0.20 Mø and a radius of R=10.4-0.78+0.86 Km, provide compelling evidence for the potential existence of exotic matter in neutron star cores. These observations offer important insights into the equation of state of dense nuclear matter. In this study, we explore the presence of negatively charged kaons and neutral anti-kaons (K- and K0) within neutron stars (NSs) using a Relativistic Mean Field (RMF) model with first order kaon condensate. To our knowledge, this is the first alternative approach aiming to simultaneously explain the observed properties of both XTE J1814-338 and HESS J1731-347 by invoking kaon condensation in dense matter. Furthermore, we compare our model with recent data from the pulsars PSR J0437-4715 and PSR J1231-1411, and argue that a two-branch scenario, each representing a distinct form of nuclear matter, may be necessary to account for the diverse range of compact astrophysical objects.